Miniaturized Coupling Structures for Decoupling PIFAs on Handheld Devices. (16th May 2016) - Li, Qian; Yu, Yaxin
Abstract : One efficient approach is introduced in this paper to reduce mutual coupling and correlation coefficient for two closely placed PIFAs in a handheld device. The approach is based on one miniaturized structure which consists of two metallic layers, printed on either side of one thin dielectric layer. Due to the small spacing between two conducting patches, high electromagnetic field is induced within the dielectric layer. The geometry and position of this structure have been modified to decouple the PIFA array at 1.9 GHz and produce maximum miniaturization thereby occupying less space on a handheld device ground plane. By employing the proposed structures, a 20 dB reduction in mutual coupling is achieved. The correlation coefficient also reduces to 0.007278. The performance of the structure is validated by both simulated results and measured data obtained from several fabricated prototypes.